Upper body heavy strength training does not affect performance in junior female cross-country skiers - Skattebo, Ø. .; Hallén, J.; Rønnestad, B. R.; Losnegard, T. (Scandinavian Journal of Medicine & Science in Sports, 2016)
We investigated the effects of adding heavy strength training to a high volume of endurance training on performance and related physiological determinants in junior female cross-country skiers. Sixteen well-trained athletes (17 ± 1 years, 60 ± 6 kg, 169 ± 6 cm, VO2max running: 60 ± 5 mL/kg/min) were assigned either to an intervention group (INT; n = 9) or a control group (CON; n = 7). INT completed two weekly sessions of upper body heavy strength training in a linear periodized fashion for 10 weeks. Both groups continued their normal aerobic endurance and muscular endurance training. One repetition maximum in seated pull-down increased significantly more in INT than in CON, with a group difference of 15 ± 8% (P < 0.01). Performance, expressed as average power output on a double poling ergometer over 20 s and as 3 min with maximal effort in both rested (sprint-test) and fatigued states (finishing-test), showed similar changes in both groups. Submaximal O2-cost and VO2peak in double poling showed similar changes or were unchanged in both groups. In conclusion, 10 weeks of heavy strength training increased upper body strength but had trivial effects on performance in a double poling ergometer in junior female cross-country skiers.